Bioluminescence : living lights, lights for living - Wilson, Therese, 1925-; Hastings, J. Woodland (John Woodland), 1927-2014 (Harvard University Press, 2013)
Bioluminescence is everywhere on earth, most of all in the ocean, from angler fish in the depths to flashing dinoflagellates at the surface. Wilson and Hastings explore the natural history, evolution, and biochemistry of the diverse array of organisms that emit light and offer an evolutionary explanation for their sporadic distribution and rarity.